Case Report: Anti-Yo antibody mediated paraneoplastic cerebellar degeneration in a patient with squamous cell lung carcinoma - Yang, Chen-Hao; Xu, Yan; Fan, Si-Yuan (Frontiers in Immunology, 2025)
Paraneoplastic cerebellar degeneration (PCD) is a heterogeneous group of neurologic syndromes associated with primary tumors. It is postulated that the immune system targets a tumor antigen that is also expressed endogenously in the nervous system. The majority of these patients are diagnosed with breast cancer or gynecological cancer, while it is exceedingly rare in lung squamous cell carcinoma (LUSC) patients. Here we reported a rare case of anti-Yo antibody-positive PCD in a patient with LUSC and got successfully treated via immunotherapy and oncological treatment. The patient’s ataxia symptoms alleviated following the administered treatments, suggesting that early immunotherapeutic intervention may have potential value in mitigating neurological deterioration. Furthermore, active and timely management of the primary carcinoma is crucial.